2018
DOI: 10.1007/s10639-017-9684-0
|View full text |Cite
|
Sign up to set email alerts
|

Affordances of mobile devices and note-taking apps to support cognitively demanding note-taking

Abstract: Note-taking is one of the more common and ever-present learning activities that form an important part of all students' daily lives. The potential of using technology to enhance note-taking activities has recently come under the spotlight. However, while mobile technologies may be applauded for their mobility and the value they can add to students' learning experience, they could easily become a distracting factor, rather than the improvement they were intended to be. In this qualitative study, eight students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…This finding might be attributed to student behaviour in typing notes on their device in a lecture theatre. Mueller and Oppenheimer (2014) [45] found that students typed the received information without processing, which prevented them from understanding content during lecture time, while van Wyk and van Ryneveld (2018) [46] discussed the benefits of mobile devices and cognitively demanding note-taking process. Based on the finding of this investigation, this process had an impact on student academic performance as they did not have enough time to process the new lecture information and to process the information from the available variety of resources at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might be attributed to student behaviour in typing notes on their device in a lecture theatre. Mueller and Oppenheimer (2014) [45] found that students typed the received information without processing, which prevented them from understanding content during lecture time, while van Wyk and van Ryneveld (2018) [46] discussed the benefits of mobile devices and cognitively demanding note-taking process. Based on the finding of this investigation, this process had an impact on student academic performance as they did not have enough time to process the new lecture information and to process the information from the available variety of resources at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…( 2018 ) specified that using mobile applications to acquire up‐to‐date knowledge for decision making could not only improve students' learning engagement and peer interactions but also had the potential to facilitate their knowledge construction. Moreover, van Wyk and van Ryneveld ( 2018 ) validated that learners who were engaged in judging and interacting with others were generally more involved in the classroom activities and had better learning achievements than those learning with traditional lecture‐based instruction. Bernardo and Santos ( 2021 ) further emphasized the importance of guiding students to acquire mobile technology–supported up‐to‐date knowledge for promoting students' learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algunas investigaciones de usos educativos con los teléfonos inteligentes incluyen: tomar notas durante las clases (Van Wyk & Van Ryneveld, 2018); intercambio de información académica, coordinación de trabajos grupales y consulta de servicios universitarios (Organista-Sandoval et al, 2013;Vázquez-Cano & Sevillano, 2015); aprendizaje de matemáticas por medio de cuestionarios interactivos para evaluación formativa (Masero, 2019); uso como herramienta de enseñanza-aprendizaje en clases de historia (Fragoso et al, 2020); organización de las sesiones educativas, resolución de dudas, envío de información, discusiones y presencia social (Raiman et al, 2017); clasificación de los estudiantes con respecto al perfil de conocimiento y uso académico del teléfono inteligente (Cruz & Barragán, 2017;Salcines-Talledo et al, 2020), así como desarrollo de habilidades cognitivas (Ramos et al, 2010), entre otros.…”
Section: Estudios De Usos Del Teléfono Inteligente En La Educaciónunclassified